The Performance and Role of PSMA PET Scans in Localised Prostate Cancer - Jianliang Liu; Jack Dunne; Karim A. Touijer; Marlon Perera; Nathan Lawrentschuk (Société Internationale d’Urologie Journal)
Background/Objectives: Prostate cancer (PCa) is one of the most prevalent cancers in men. While PSA testing aids in early detection, it often identifies clinically insignificant PCa (ciPCa), which may not necessitate treatment. Prostate-specific membrane antigen (PSMA) PET scans have emerged as a promising tool to evaluate of localised PCa. This review aims to assess the current evidence of using PSMA PET scans for localised PCa. Methods: Peer-reviewed publications on PSMA PET scans in localised PCa, from inception to May 2024, were retrieved from PubMed. The outcomes evaluated included diagnostic performance in identifying intraprostatic lesions, detecting csPCa (ISUP GG ≥ 2), and role peri-treatment. Results: The addition of PSMA PET/CT to MRI improved the sensitivity (from 83% to 97%) and NPV (72% to 91%) of detecting csPCa. PSMA PET helped improve risk stratification in active surveillance by identifying MRI-occult lesions in up to 29% of patients, of which up to 10% may harbour underlying unfavourable pathology. In local staging, PSMA PET/MRI outperforms MRI in identifying extra-prostatic extension (77% vs. 73%) and seminal vesicle invasion (90% vs. 87%). PSMA PET scans are also superior to MRI in nodal staging and bone scans in identifying bony metastasis. PSMA PET scans appear useful in guiding treatment of localised PCa and aiding follow-up. Conclusions: PSMA PET scans are valuable for evaluating localised PCa by improving the detection of csPCa and enhancing local staging. However, most available studies are retrospective, and long-term oncological outcomes remain underreported due to the relative novelty of PSMA PET scans.